Secondary Alveolar Bone Grafting (CLEFTSiS) 2007–2010. (March 2016) - Paterson, Michael; Rae, Jennifer; Paterson, Paul; Gilgrass, Toby; Devlin, Mark; McIntyre, Grant
Objective: To determine whether alveolar bone graft outcomes for unilateral and bilateral cleft lip and palate patients have continued to improve since the reorganization of cleft services in Scotland in 2000. Design: Retrospective analysis of postoperative anterior occlusal radiographs. Patients and Participants: Eighty-one of 106 patients who were eligible for alveolar bone grafting between 2007 and 2010 had suitable postoperative radiographs available. Interventions: Twenty-seven percent of the patients (n = 22) had presurgical orthodontic intervention. All patients underwent alveolar bone grafting with bone harvested from the iliac crest. Main Outcome Measures: The Kindelan bone-fill index was used to evaluate success. Weighted kappa statistics were used to assess intra- and interobserver reproducibility. A comparison was made with results from 2000 to 2004 to assess any improvement. Chi-square tests (or Fisher exact test) were used to determine whether outcomes differed depending on the laterality of the cleft, use of presurgical expansion, or age at bone grafting. Result: Interobserver scoring agreement was good (weighted kappa = .383). Intraobserver reproducibility was greater (weighted kappas of .835 and .620). Success was achieved in 99% of bone grafts, compared with 76% in the period from 2000 to 2004 (P < .001). There was no statistically significant relationship between the laterality of the cleft (P = 1.000), use of presurgical expansion (P = 1.000), or age at time of bone grafting and outcome (P = .259). Conclusion: Scottish secondary alveolar bone graft outcomes improved during 2007 to 2010 in comparison to the 2000 to 2004 results.